Minat Menabung di Bank Syariah - Arwin Arwin (IPM2KPE, 2023)
This study aims to determine the interest in saving Islamic boarding school students Darul Ikhlas Padangsidimpuan at Indonesian Sharia banks. This research method is quantitative. The data used are primary and secondary data, using questionnaires, books, and journals and the type of sampling using purposive sampling method. The sample in this study was the Darul Ikhlas Padangsidimpuan Islamic Boarding School students, totaling 177 respondents. The analysis technique in this study used multiple linear regression in SPSS software. The results showed that a) the calculated t value for the promotion variable was 1.448 ≤ 1.973 (t table), with a significant value of 0.149 ≥ 0.05; b) the calculated t value for the religiosity variable is 3.338 ≥ 1.973 (t table), with a significant value of 0.01≤ 0.05; c) the calculated t value for the knowledge variable can be obtained 4.978 ≥ 1.973 (t table), with a significant value of 0.00 ≤ 0.05. In conclusion, simultaneously the interest in saving for Darul Ikhlas Padangsidimpuan Islamic Boarding School students in Islamic banks is jointly influenced by promotion, religiosity and knowledge. And the results of the partial test of promotion, religiosity and knowledge variables have a significant positive effect on the intention to save Islamic boarding school students Darul Ikhlas Padangsidimpuan. Keywords: Islamic Bank, Saving, Interest, Santri